2007
DOI: 10.1111/j.1601-183x.2007.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Why do young women smoke? V. Role of direct and interactive effects of nicotinic cholinergic receptor gene variation on neurocognitive function

Abstract: Previous work suggests that young women who smoke cigarettes regularly, or did so in the past, manifest a neurocognitive profile that is characterized by small but significant impairments of response inhibition and attention. The present study sought to determine whether variation in nicotinic cholinergic receptor (nAchR) genes impacts upon cognitive function in these domains by overall or differential effects on the performance of current, former and non-smokers. The study sample consisted of 100 female colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 33 publications
3
48
1
1
Order By: Relevance
“…Among many interesting examples of proteins at the network periphery that may be under positive selection are the protein encoded by the CHRNA5 (ENSG00000169684) gene, neuronal acetyl-choline receptor subunit ␣-5; this integral membrane protein is involved in neuronal processes likely to be under ongoing adaptation, and CHRNA5 was recently associated with several cognitive performance criteria (34). Another protein, the Ficolin-3 protein encoded by the FCN3 gene (ENSG00000142748), is a secreted protein that exerts lectin activity and is presumably involved in innate immunity through binding to bacterial lipopolysaccharides (35).…”
Section: Discussionmentioning
confidence: 99%
“…Among many interesting examples of proteins at the network periphery that may be under positive selection are the protein encoded by the CHRNA5 (ENSG00000169684) gene, neuronal acetyl-choline receptor subunit ␣-5; this integral membrane protein is involved in neuronal processes likely to be under ongoing adaptation, and CHRNA5 was recently associated with several cognitive performance criteria (34). Another protein, the Ficolin-3 protein encoded by the FCN3 gene (ENSG00000142748), is a secreted protein that exerts lectin activity and is presumably involved in innate immunity through binding to bacterial lipopolysaccharides (35).…”
Section: Discussionmentioning
confidence: 99%
“…30,31 CHRNA2 is a broadly-expressed subunit of nicotinic acetylcholine receptors. 32 In addition to its role in nicotine dependence and neurocognitive functioning, 33,34 CHRNA2 is located in a region of chromosome 8p that is suggested to contribute to psychiatric and neurodegenerative disorders. 35 Interestingly, nominal differential methylation of CHRNA2 was recently reported in monozygotic twins discordant for psychosis.…”
Section: Subject Enrollment Subjects Were Recruited From the Specialmentioning
confidence: 99%
“…81,188,189 Before dependence on nicotine is established, factors such as these (as well as genetic factors) influence the likelihood of initiating smoking (SI) which is a prerequisite for ND to develop. A further complexity that must be taken into account is that personality, psychopathology and cognitive function are themselves influenced by genetic factors.…”
Section: General Overviewmentioning
confidence: 99%
“…209 We suggest that the improvement by nicotine of cognitive function in these domains may predispose young women who initiate cigarette smoking to maintain the habit. 209 Subsequently, Rigbi et al 189 showed that the performance on the relevant test measures (for example, response inhibition) is modified by specific variants in nAChR genes, mostly in CHRNA4, CHRNA7 and CHRNB3 but also in other nAChR genes. 189 nAChR genes, neuroticism and ND A connection between neuroticism and smoking is well established, both in adults and adolescents.…”
Section: General Overviewmentioning
confidence: 99%
See 1 more Smart Citation